ANALYSIS OF LICENSING SERVICES FOR MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN KANTOR CAMAT GUNUNG MERIAH KABUPATEN ACEH SINGKIL - Raudah, Raudah; Nasution, Lia Nazliana; Rusiadi, Rusiadi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This study aims to analyze the influence of technology, human resources, and infrastructure on MSME licensing services at the Gunung Meriah Sub-district Office, as well as the influence of all three simultaneously. The study used 150 respondents whose data were collected through questionnaires and analyzed using the Multiple Linear Regression method. The background of this study is the importance of public services as an interaction between the community and the government to meet the needs of goods, services, or administrative services, as regulated in Law No. 25 of 2009 which states that the purpose of public services is to improve community welfare. However, MSME licensing services at the Gunung Meriah Sub-district Office, Aceh Singkil Regency, still face various obstacles such as long and complicated processes, difficult bureaucracy, lack of understanding of officers, limited facilities, and suboptimal technology. To overcome these obstacles, system improvements, service quality improvements, and more effective socialization are needed. The results of the study indicate that partially technology, human resources, and infrastructure each have a significant influence on MSME licensing services. Simultaneously, the three variables also have a significant effect on MSME licensing services at the Gunung Meriah Sub-district Office.